Temporary stabilization of air pollution control residues using carbonation - Zhang, Hua (Waste management (New York, N.Y.), 2008)
Carbonation presents a good prospect for stabilizing alkaline waste materials. The risk of metal leaching from carbonated waste was investigated in the present study; in particular, the effect of the carbonation process and leachate pH on the leaching toxicity of the alkaline air pollution control (APC) residues from municipal solid waste incinerator was evaluated. The pH varying test was conducted to characterize the leaching characteristics of the raw and carbonated residue over a broad range of pH. Partial least square modeling and thermodynamic modeling using Visual MINTEQ were applied to highlight the significant process parameters that controlled metal leaching from the carbonated residue. By lowering the pH to 8-11, the carbonation process reduced markedly the leaching toxicity of the alkaline APC residue; however, the treated APC residue showed similar potential risk of heavy metal release as the raw ash when subjected to an acid shock. The carbonated waste could, thereby, not be disposed of safely. Nonetheless, carbonation could be applied as a temporary stabilization process for heavy metals in APC residues in order to reduce the leaching risk during its transportation and storage before final disposal